Correction to: factors affecting residents transition from long term care facilities to the community: a scoping review - Shannon Freeman; Kristen Bishop; Lina Spirgiene; Erica Koopmans; Fernanda C. Botelho; Trina Fyfe; Beibei Xiong; Stacey Patchett; Martha MacLeod (BMC, 2017)
Abstract ᅟ